(untitled) (Fiep Bulletin - online, 2013)
This study aimed to examine the representations of teachers and students about the role of physical education in schools. The approach was used with the qualitative information collected through semi-structured and interpreted by analysis of content. Participants were three teachers of Physical Education and twelve students of the discipline of the Finals Series elementary school, one teacher and four students from each school’s school system. Thus, this research highlighted the controversial issue as well, wrong, the role that physical education has to face students. Considering that, teachers and students interviewed believe that Fitness assumes his role at the time it promotes health and some sports teaches. From there, it becomes clear the commitment of professionals who work with the training of students and teachers to be revising their notions about the role that physical education must take today to the transformations that were part of their history and also contributed to its formation in the field of education.